Digital Workbooks in Flipped Nutrition Education: Student Perspectives' - Sarah Burkhart; Dana Craven (MDPI AG, 2020)
Nutrition and dietetic (N&D) education is traditionally taught didactically; however, the flipped classroom approach (FCA) is an emerging pedagogical approach in this discipline. Technological tools providing cognitive support enhance learning, particularly when students are engaged. In N&D education, students have reported the FCA as engaging; however, evidence for how best to integrate technologies into the FCA is limited. The aim of this research is to explore undergraduate nutrition and dietetic students' self-reported perceptions of the use of a digital workbook in nutrition courses designed and delivered using an FCA. A cross-sectional self-administered online survey was utilised to investigate Australian undergraduate student (N = 39) satisfaction, frequency of use, engagement with, and usefulness of a digital workbook. Most students (87%) were satisfied/very satisfied with the digital workbook as a tool for learning, applying and consolidating/revising course content. Most students (95%) agreed the digital workbook was engaging, providing comments related to workbook design, encouraged participation and novelty. Most useful aspects reported were workbook structure, development of a learning artefact, self-directed aspects and convenience, whereas, least useful aspects included technological issues. The use of a digital workbook in N&D education was well received and is an innovative approach to delivering courses taught with an FCA.